Application of thermoelectric cooling and heating to control the temperature of irrigation fluid in ophthalmic surgery - Kobylianskyi, R.R.; Lysko, V.V.; Pasyechnikova, N.V.; Umanets М.М.; Zadorozhnyy О.S.; Rozver, Yu.Yu.; Babich А.О. (Physics and Chemistry of Solid State, 2025)
The paper considers the possibilities of using thermoelectric cooling and heating irrigation fluid during ophthalmic surgery. A comparative analysis of the use of compression, cryogenic and thermoelectric devices in the required temperature range of irrigation solutions at an ambient temperature of about 20°C is carried out. The advantages of using devices based on thermoelectric cooling (heating) in medical practice are shown. The results of the design and study of the parameters of a thermoelectric device to ensure the optimal temperature of the irrigation fluid during ophthalmic operations are presented.